Pengembangan Aplikasi Heal&Go Sebagai Sebuah Sistem Rekomendasi Destinasi Wisata Berbasis Mobile - Yudha, I Wayan Pande Putra; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Indonesia is a country that has a variety of attractive tourist locations such as beautiful inland or rural areas, diverse historical and cultural heritage, beautiful beaches, and much more. Then because Indonesia is currently transitioning into a new normal era, many people want to take a vacation by traveling to various tourist attractions in Indonesia, but a lot of people are confused about choosing their tourist attractions. Therefore, the author makes a mobile-based application that serves to help people choose a travel destination based on their respective preferences. Heal&Go is an app that can recommend perfect destinations for these people based on their preferences and can interact with users for immediate feedback and dynamic adaptation. Then with the development of the Heal&Go application with the Prototyping method and also the Kotlin programming language in its development, it is hoped that it can help the community in choosing their next travel destination.